Long-term rotational and emission variability of 17 radio pulsars. Issue 4 (29th April 2022) - Shaw, B; Stappers, B W; Weltevrede, P; Brook, P R; Karastergiou, A; Jordan, C A; Keith, M J; Kramer, M; Lyne, A G
ABSTRACT: With the ever-increasing sensitivity and timing baselines of modern radio telescopes, a growing number of pulsars are being shown to exhibit transitions in their rotational and radio emission properties. In many of these cases, the two are correlated with pulsars assuming a unique spin-down rate (ν ) for each of their specific emission states. In this work, we revisit 17 radio pulsars previously shown to exhibit spin-down rate variations. Using a Gaussian process regression (GPR) method to model the timing residuals and the evolution of the profile shape, we confirm the transitions already observed and reveal new transitions in 8 yr of extended monitoring with greater time resolution and enhanced observing bandwidth. We confirm that seven of these sources show emission-correlated ν transitions (Δ ν ), and we characterize this correlation for one additional pulsar, PSR B1642−03. We demonstrate that GPR is able to reveal extremely subtle profile variations given sufficient data quality. We also corroborate the dependence of Δ ν amplitude on ν and pulsar characteristic age. Linking Δ ν to changes in the global magnetospheric charge density Δρ, we speculate that ν transitions associated with large Δρ values may be exhibiting detectable profile changes with improved data quality, in cases where they have not previously been observed.